Local Wisdom: The Bau Lolon Rite as A Policy Model for Making Village Regulations in Witihama District, East Flores Regency - Tokan, Frans Bapa; Lamawuran, Yosef Dionisius; Bidi, Maximianus Ardon; Susu, Mikael Thomas; Kosat, Emanuel (Universitas Teuku Umar, 2025)
This study aims to explore and analyze whether the village government can make and implement village regulations based on local knowledge as a basis for improving and enriching the quality of village regulations. So far, the process of making village regulations has focused more on the formal legal aspects and tends to ignore local values and aspirations of the wider community. As a result, the village regulation products stipulated in several villages in Witihama District do not have a solid basis of social legitimacy and broad support from the village community. This study uses a qualitative descriptive method with in-depth interview (FGD) data collection techniques, observation and documentation to reveal the values contained in the Bau Lolon rite that can be integrated into the process of making village regulations. The results of the study show that the policy model for making village regulations through the Bau Lolon local wisdom approach can achieve successful implementation because it focuses more on community needs and receives social support. In conclusion, incorporating local wisdom such as the Bau Lolon ritual in policy processes is not merely symbolic but a strategic step towards more inclusive, culturally grounded, and sustainable village governance.